Analysis of Sexual Education in Adolescents (Study Of The Qur'an Surah An-Nur Verses 30-31) - Reza Rahmadani (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2020)
Thesis, Islamic Religious Education Study Program, July 2020. This study aims to gain awareness and further exploration of sexual education in adolescents and provide a deeper understanding of sexual education that has been written in the Qur'anic verse. This research uses library research or literature study research to obtain the research data needed. The data collection technique uses the documentation method. The technique of validity of data by combining data into descriptive. The data analysis technique used the content analysis method. The results in this study indicate that the contents of the content of Surah an-Nur verses 30-31 according to the commentators are education regarding the purification of the soul, advice to guard one's view, maintain genitals, cover genitals, know about mahram, muamalah, and the command to repent to Allah when you find it. Self negligent from the teachings of Allah SWT.